PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA APARAT PEMERINTAH DAERAH DENGAN BUDAYA ORGANISASI, MOTIVASI, DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING - Wiguna, Lalu Yoga Putra; Sukartha, I Made; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p05, 2017)
This study aims to examine the effect of budget participation on the performance of conditional factors (organizational culture, motivation, and leadership style). Performance tested was the performance of government officials in North Lombok regency. Specifically, this research examines the influence of budget participation on the performance, as well as the effect of budget participation on the performance of the organizational culture, motivation, and leadership style as a moderating variable. The research was conducted by survey by distributing questionnaires to officials directly involved in the budgeting process, the three officials in each of the regional work units (SKPD). The questionnaire can be used amounted to 93 questionnaire. Data analysis was performed using Moderated Regression Analysis (MRA) The results showed (1) budget participation has positive influence on the performance of government officials; (2) moderate the influence of organizational culture, motivation, and The leadership style moderating influence of budget participation with the performance of government officials
Keywords: the performance of government officials, budget participation, organizational culture, motivation, and The leadership style